Report on the National Workshop on Nutrition/Health Education and the Promotion and Use of Indigenous Foods (National Centre for Educational Resource Development GeorgetownGY, 1986)
Outlines in chronological order the proceedings of the workshop which include presentations, discussions, films and practical group work. Covers topics such as existing agricultural roles, policies and programmes in Guyana, food habits and consumption of the Guyanese population, and the development of the weaning food project in the concept of social marketing. Identifies three kinds of messages and strategies for promoting the use of indigeneous foods, which are geared to target groups such as children, adults, and senior citizens.
DC